THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN DRIVING MOTIVATION AND IMPROVING ORGANIZATIONAL PERFORMANCE - Densius Amamehi; Pungki (Journal Informatic, Education and Management (JIEM), 2026)
Transformational leadership style is a leadership style that focuses on the leader's ability to inspire , motivate , and encourage positive change in members of the organization . This writing aims to analyze the influence of transformational leadership on increasing the motivation and performance of members in the organization . The method used in this research is a qualitative approach with library study techniques from various journals , books , and relevant scientific articles . The results of the discussion show that transformational leadership has an important role in creating a productive work environment , increasing member loyalty , and building a higher work spirit . In addition , a transformational leader is able to provide a clear vision , develop good communication , and be a role model for members in the organization . Therefore , transformational leadership can be one of the effective strategies in improving the quality of human resources and organizational success .